Grit among college students: social or personal? - Wong, Bridgette Tsin Ee; Prihadi, Kususanto Ditto; Ashok, Arman Imran; Huan, Tan Li; Jamaluddin, Anne (Intelektual Pustaka Media Utama, 2025)
Grit, the personal characteristic of perseverance and passion for long-term goals, plays a vital role in college students' success and well-being. This study aimed to investigate the contribution of optimism (a personal factor) and college mattering (a social factor), as well as their underlying mechanism on grit among college students. Data was collected from 186 participants from Selangor, Malaysia, who voluntarily responded to the college mattering scale (CMS), life orientation test-revised (LOT-R), and grit scale (Grit-S) Scale. The Bootstrap method with 5,000 resamples at a 95% confidence interval was employed for analysis. Our findings suggested that while college mattering and optimism did not significantly predict grit when controlling for each other, both social and personal factors are similarly important in predicting the development of grit, and that any intervention program or module to improve the students’ grit must encompass both social development and the improvement of social dynamics in the academic institutions.